Direct Comparison of 4 Very Early Rule-Out Strategies for Acute Myocardial Infarction Using High-Sensitivity Cardiac Troponin I - Boeddinghaus, Jasper; Nestelberger, Thomas; Twerenbold, Raphael; Wildi, Karin; Badertscher, Patrick; Cupa, Janosch; Bürge, Tobias; Mächler, Patrick; Corbière, Sydney; Grimm, Karin; Giménez, Maria Rubini; Puelacher, Christian; et al. (Circulation, 2017)
BACKGROUND: Four strategies for very early rule-out of acute myocardial infarction using high-sensitivity cardiac troponin I (hs-cTnI) have been identified. It remains unclear which strategy is most attractive for clinical application. METHODS: We prospectively enrolled unselected patients presenting to the emergency department with symptoms suggestive of acute myocardial infarction. The final diagnosis was adjudicated by 2 independent cardiologists. Hs-cTnI levels were measured at presentation and after 1 hour in a blinded fashion. We directly compared all 4 hs-cTnI-based rule-out strategies: limit of detection (LOD, hs-cTnI<2 ng/L), single cutoff (hs-cTnI<5 ng/L), 1-hour algorithm (hs-cTnI<5 ng/L and 1-hour change<2 ng/L), and the 0/1-hour algorithm recommended in the European Society of Cardiology guideline combining LOD and 1-hour algorithm. RESULTS: Among 2828 enrolled patients, acute myocardial infarction was the final diagnosis in 451 (16%) patients. The LOD approach ruled out 453 patients (16%) with a sensitivity of 100% (95% confidence interval [CI], 99.2%-100%), the single cutoff 1516 patients (54%) with a sensitivity of 97.1% (95% CI, 95.1%-98.3%), the 1-hour algorithm 1459 patients (52%) with a sensitivity of 98.4% (95% CI, 96.8%-99.2%), and the 0/1-hour algorithm 1463 patients (52%) with a sensitivity of 98.4% (95% CI, 96.8%-99.2%). Predefined subgroup analysis in early presenters (≤2 hours) revealed significantly lower sensitivity (94.2%, interaction P=0.03) of the single cutoff, but not the other strategies. Two-year survival was 100% with LOD and 98.1% with the other strategies (P<0.01 for LOD versus each of the other strategies). CONCLUSIONS: All 4 rule-out strategies balance effectiveness and safety equally well. The single cutoff should not be applied in early presenters, whereas the 3 other strategies seem to perform well in this challenging subgroup. CLINICAL TRIAL REGISTRATION: URL: http://www.clinicaltrials.gov. Unique identifier: NCT00470587.
Keywords: senioři; Decision Support Techniques; elektrokardiografie; algoritmy; Up-Regulation; senioři nad 80 let; metody pro podporu rozhodování; Algorithms; upregulace; Europe; troponin I; Predictive Value of Tests; Prognosis; Time Factors; sexuální faktory; Kaplan-Meier Estimate; Evropa; Middle Aged; Risk Assessment; myocardial infarction; mužské pohlaví; infarkt myokardu; prediktivní hodnota testů; Kaplanův-Meierův odhad; Prospective Studies; Adult; Myocardial Infarction; věkové faktory; Aged, 80 and over; Electrocardiography; ženské pohlaví; prognóza; hodnocení rizik; Humans; prospektivní studie; Sex Factors; biologické markery; časové faktory; lidé středního věku; diagnosis; Health Status; rizikové faktory; Age Factors; akutní koronární syndrom; Troponin I; dospělí; zdravotní stav; Biomarkers; rule-out strategies; Female; Aged; Risk Factors; Acute Coronary Syndrome; lidé; Male